(untitled) (Revista Iberoamericana de Bioética, 2024)
The 21st century arrived together with the news of a “next wave”: Artificial Intelligence (AI). We urgently need to broaden the debate on the limits of science, emphasizing the development of bioethical mechanisms to address forthcoming technological advances. We should be asking ourselves: what are the possible impacts of AI on future generations? How can we prevent socially disadvantaged people from becoming even more vulnerable through the use of AI? In the form of a critical literature review, this study aims to reflect on the potential of AI to build a fairer and more socially peaceful world. The study concludes that there is a shortage of bioethical studies of AI that engage principles such as human dignity, human rights and fundamental freedoms. Meanwhile, today’s world is creating hybrid subjectivities which, like our increasingly “humanized” machines, are displayed as virtual realities that can only detract from the very real concrete demands and problems faced by communities.